2013
DOI: 10.3109/13645706.2013.827122
|View full text |Cite
|
Sign up to set email alerts
|

Systems and technologies for objective evaluation of technical skills in laparoscopic surgery

Abstract: Minimally invasive surgery is a highly demanding surgical approach regarding technical requirements for the surgeon, who must be trained in order to perform a safe surgical intervention. Traditional surgical education in minimally invasive surgery is commonly based on subjective criteria to quantify and evaluate surgical abilities, which could be potentially unsafe for the patient. Authors, surgeons and associations are increasingly demanding the development of more objective assessment tools that can accredit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 53 publications
0
4
0
Order By: Relevance
“…Studies have shown that skills acquired during simulation training could be transferred to the operating room [7]. A number of objective assessment tools for surgical skills, including motion analysis, have been developed for use with surgical simulators [8,9]. Most of these systems are based on scoring methods [10], carousel of tasks with sensors for monitoring metrics [11] and instrument motion tracking [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies have shown that skills acquired during simulation training could be transferred to the operating room [7]. A number of objective assessment tools for surgical skills, including motion analysis, have been developed for use with surgical simulators [8,9]. Most of these systems are based on scoring methods [10], carousel of tasks with sensors for monitoring metrics [11] and instrument motion tracking [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Evidence exists to validate motion analysis for use in laparoscopic skills assessment [17]. Indicative of its growing validity is that most available virtual reality simulators and hybrid models have incorporated motion metrics into the measurements reported to the user [8,9]. Motion analysis methods compute metrics to quantify motion information concerning the use of the surgical instruments to establish the surgical dexterity level of surgeons.…”
Section: Introductionmentioning
confidence: 99%
“…Laparoscopic suturing is more arduous than open surgery suturing [11], and the suturing procedure for laparoscopy is challenging because laparoscopic surgery requires handling of specially designed tools and requires a small vision view to reduce the size of the wound, which is not the same as the conventional open method [12,13]. It is not easy to control the needle and the distance and direction of the needle going in and out of the tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Firstly, it is a noncontact measurement method that does not require much modification to the measurement target, does not require the use of cables to transfer data, and does not require a marker to be placed on the measured target. Secondly, the use of electromagnetic equipment is inevitable in the actual surgical environment, and this inevitably interferes with the electromagnetic positioning system [14][15][16], whereas the optical capture system is not affected. The disadvantage is that there must not be an obstacle between the marker point to be measured and the optical tracking system to block the propagation of light, which can be solved by the proper design and installation of the marker point.…”
Section: Introductionmentioning
confidence: 99%